Адаптивні стратегії полікультурної дискурсивної особистості в англомовному комунікативному просторі - Котов, М.В. (My University, 2016)
The paper focuses on meaning formation during the process of discursive adaptation in the English communicative space. It studies the properties of realization of adaptation strategies and typical guidelines which are actualized within the process of communication of a polycultural discursive personality depending on discursive surroundings and the stage of adaptation. Typical guidelines optimizing the realization of adaptation strategies by a polycultural discursive personality include “tolerance to ambiguity”, “behavioral flexibility”, “communicative awareness”, “knowledge discovery”, “respect for otherness”, and “empathy”. The realization of cooperative and non-cooperative strategies has been characterized depending on discursive surroundings, taking into consideration the properties of interaction of verbal and non-verbal communicative components. The cooperative strategy includes the tactics of intimacy achievement, manipulated intimacy achievement, learning, positive stereotyping. The non-cooperative strategy embraces the tactics of negative stereotyping, manifestation of alienation, strict ethnocentrism, and manifestation of aggression.
Adaptation Strategies of a Polycultural Discursive Personality in the English Communicative Space
Key words: discursive adaptation, communicative space, polycultural discursive personality, guideline, adaptation strategy, tactic, discursive surroundings, verbal, non-verbal.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics::Linguistic subjects::Linguistics; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics::Other Germanic languages::English language